1997
DOI: 10.1093/ije/26.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and its correlates in Chinese adult populations, urban and rural, of Beijing. The PRC-USA Collaborative Study in Cardiovascular and Cardiopulmonary Epidemiology

Abstract: In addition to its strong association with body mass index, SUA is independently related to serum lipids, particularly triglycerides, and to serum glucose. While some of the univariate relation of SUA to BP is apparently due to the strong relation of body mass to both SUA and BP, a low order significant relation between SUA and BP remains with control for BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 0 publications
0
23
1
Order By: Relevance
“…Furthermore, SUA is independently related to BMI, serum lipids, particularly TG, and to serum glucose. While some of the relation of SUA to BP is apparently due to the strong relation of BMI to both SUA and BP, a low order significant relation between SUA and BP remains after controlling for BMI (26). In our study, those risk factors were also associated with a higher SUA level.…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, SUA is independently related to BMI, serum lipids, particularly TG, and to serum glucose. While some of the relation of SUA to BP is apparently due to the strong relation of BMI to both SUA and BP, a low order significant relation between SUA and BP remains after controlling for BMI (26). In our study, those risk factors were also associated with a higher SUA level.…”
Section: Discussioncontrasting
confidence: 47%
“…Recent findings show that the occurrence of gout is increasing in China [27], possibly due to changes in dietary habits. The treatment of gout entails the use of several classes of therapeutic agents such as xanthine oxidase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiologic data indicated that the incidence of primary gout has increased by 2-fold over the past 20 years (Arromdee et al, 2002). This disease is also rapidly rising in China (Li et al, 1997), due probably to recent changes in dietary habits. Hyperuricemia is a hallmark of gout (Rott and Agudelo, 2003).…”
mentioning
confidence: 99%